Implementation of visible light positioning (VLP) on embedded FPGA board - Lalithraj, Gundu Praksham (2019)
In this dissertation, a visible light positioning (VLP) approach based on adapted phase difference of arrival (PDOA) algorithm is implemented on an embedded Field- Programmable Gate Array (FPGA) board. With the support of Xilinx ISE® design suite and python integrated development environment, I have developed an FPGA program and a GUI application on Raspberry Pi to locate users and plot the estimated position coordinates by sequential means of 1) obtaining analog-digital convertor signal 2) filtering and demodulation of signals using FPGA device for time difference of arrival (TDOA) measurements 3) trilateration and interfacing implemented in Raspberry Pi to determine the position coordinates. I have also designed the user interface with necessary prompts and error messages for visualizing the results to the users. In this project, a low complexity PDOA algorithm and its implementation on embedded system will be explained in detail. A real-time experiment based on ideal scenarios has been carried out to evaluate the feasibility and performance of the embedded VLP system in term of its accuracy. The results show that the high accuracy of 2D positioning can be achieved. In general, this dissertation has successfully validated an embedded 2D VLP scheme using PDOA algorithm with low complexity and high accuracy.